Freshman's perceptions in electrical/electronic engineering courses: early findings - Leão, Celina Pinto (2015)
The present study reports early findings on freshman's perceptions in Electrical/Electronic Engineering courses from four higher education institutions: two Portuguese (Instituto Superior de Engenharia do Porto, ISEP, and Universidade do Minho, UM) and two Brazilian (Instituto Federal de Santa Catarina, IFSC, and Universidade Regional de Blumenau, FURB).This study was based on a questionnaire previously validated that contains two main parts: student characterization and a list of forty-four items, divided in six groups (Teacher Involvement Perception, Student Interest, Student-Teacher interaction, Course organization and functioning, Infrastructures and Overall satisfaction) classified in a 5-point agreement Likert scale: 1 (Strongly Disagree) and 5 (Strongly Agree), with the neutral point being neither disagree nor agree. The goal of the research was to look for similarities and differences regarding the course organization and functioning, students' interest in the course, students' findings towards teachers' involvement and personal interaction.In the present study only data from the first three groups of the questionnaire will be analyzed. This questionnaire was answered by a total of 257 students from the four institutions.This is a preliminary study where only major conclusions are drawn: the results of the students' evaluations are positive in all items analysed with a score higher than 3.0. The highest scores were obtained in two items of the factor Student Interest.Presently the validated questionnaire has been extended to all academic years to study in the future possible differences on students' perceptions. To assess the influence of cultural differences and identify the similarities and differences referred above it will be necessary to perform a more detailed analysis of all items/factors.